2017
DOI: 10.1371/journal.pone.0175599
|View full text |Cite
|
Sign up to set email alerts
|

Cytoskeletal stability and metabolic alterations in primary human macrophages in long-term microgravity

Abstract: The immune system is one of the most affected systems of the human body during space flight. The cells of the immune system are exceptionally sensitive to microgravity. Thus, serious concerns arise, whether space flight associated weakening of the immune system ultimately precludes the expansion of human presence beyond the Earth's orbit. For human space flight, it is an urgent need to understand the cellular and molecular mechanisms by which altered gravity influences and changes the functions of immune cells… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
66
0
3

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
4

Relationship

2
7

Authors

Journals

citations
Cited by 66 publications
(73 citation statements)
references
References 72 publications
4
66
0
3
Order By: Relevance
“…Numerous studies have been conducted on a myriad of cell types highlighting morphological sensitivity to microgravity (Ingber, 1999;Vorselen et al, 2014), with the first documented morphological change reported by Rijken et al (1991). Morphological changes as a result of microgravity conditions, either real or simulated, have been shown to have altered transcription, translation, and organization of cytoskeletal proteins (Vassy et al, 2001;Infanger et al, 2006b;Tauber et al, 2017). Fundamental work carried out by Tabony, Pochon, and Papaseit showed that while tubulin self-assembly into microtubules occurs independent of gravity, the assembly and organization of the microtubule network is gravity dependent (Papaseit et al, 2000;Tabony et al, 2002).…”
Section: The Impact Of Microgravity Of Cell Cytoskeletonmentioning
confidence: 99%
See 1 more Smart Citation
“…Numerous studies have been conducted on a myriad of cell types highlighting morphological sensitivity to microgravity (Ingber, 1999;Vorselen et al, 2014), with the first documented morphological change reported by Rijken et al (1991). Morphological changes as a result of microgravity conditions, either real or simulated, have been shown to have altered transcription, translation, and organization of cytoskeletal proteins (Vassy et al, 2001;Infanger et al, 2006b;Tauber et al, 2017). Fundamental work carried out by Tabony, Pochon, and Papaseit showed that while tubulin self-assembly into microtubules occurs independent of gravity, the assembly and organization of the microtubule network is gravity dependent (Papaseit et al, 2000;Tabony et al, 2002).…”
Section: The Impact Of Microgravity Of Cell Cytoskeletonmentioning
confidence: 99%
“…Osteosarcoma cells (ROS 17/2.8) Cell morphological change to rounded shape with long cytoplasmic extensions 4 days and 6 days Guignandon et al, 1997 Osteosarcoma cells (ROS 17/2.8) Reduction in cell spread area and vinculin spot area, actin and focal adhesion, and stress fibers 12 and 24 h Guignandon et al, 2003 Breast cancer (MCF-7) Disoriented microtubule 1.5 h Vassy et al, 2003 Thyroid cancer (ML-1) Actin fiber reorganization Parabola flight Ulbrich et al, 2011 Human macrophages No effect on cytoskeletal structure 11 days Tauber et al, 2017 Human chondrocytes Effect on cell cytoplasm, microtubule network disruption, loss of stress fibers, actin fiber reorganization.…”
Section: Cell Type Effects Of Cells Microgravity Exposure Time Referementioning
confidence: 99%
“…8 Together, data from the International Space Station, Skylab, and space shuttle suggest that dysregulated immune cell-mediated cytokine secretion is a major mechanism leading to spaceflightassociated immune dysfunction. 5,[9][10][11][12] For example, after space travel, shifts occur in circulating cytokines, including increased levels of T lymphocytes producing IL-4, IL-8, IL-17, and IFN-γ 8,13,14 and decreased production of IL-1, IL-6, IL-12, and TNF-α in monocytes/ macrophages. [15][16][17][18] However, the causes of these immune cell dysfunctions and the associated changes in innate (macrophages and NK cells) and adaptive (T-cell) functions have not been extensively and systematically examined.…”
Section: Introductionmentioning
confidence: 99%
“…In unseren Studien untersuchten wir Signaltransduktionskaskaden [3,[6][7][8], Adhäsionsmoleküle [9][10][11], Stoffwechsel [11], funktionelle Parameter [12,13], Genexpressionsreaktionen [6,[14][15][16][17][18][19]…”
Section: Erkenntnisse Aus Unseren Studienunclassified